Resurgence of artificial intelligence in healthcare: A survey - Bera, Soumyajit; Bali, Simranpreet Kour; Kaur, Ravinder (AIP conference proceedings, 2023)
Artificial Intelligence (AI) is a broad conceptual subject of computer engineering which aims to duplicate, evaluate, or improve the decision-making system of humans. Artificial Intelligence and Machine Learning have had a significant impact on nearly every aspect of modern life, including entertainment, commerce, and healthcare. Artificial Intelligence is ready to assist individuals with a variety of activities ranging from the organizational to the medical record keeping to patient engagement, as well as specialised help such as image analysis for any report. Automating medical devices, as well as monitoring the patient’s status. However, it is widely assumed that AI technologies may be used to facilitate and enhance human labour, but that they cannot replace the work of physiotherapists. In the sphere of medicine, Artificial Intelligence and Machine Learning systems have greatly enhanced health care by significantly delivering earlier disease diagnoses or recommending ideally personalised treatment approaches. With the advancement of AI technology, the concept of smart healthcare has risen to the fore, with the potential to completely revolutionise the traditional medical system, making it more efficient, convenient, and individualized. The key technologies that support smart health care will be examined first in this review article, followed by an evaluation of the current state of smart health care that incorporates Artificial Intelligence in a range of sectors. Then, in order to strengthen the concept of smart health care, it’ll go over the challenges that exist in the smart health care system and try to come up with a strategy to fix them. Finally, this paper consider and assess the extent of this smart health-care concept.